Piante ed ebbrezze - Clauser, Marina (Firenze University Press, 2010)
Among his numerous interests, the scholar Paolo Mantegazza (1831-1910) also devoted himself to psychotropic plants, which he described in monographic contributions and in popular writings of a medical character, more specifically Quadri della natura umana: Feste ed ebbrezze and Elementi di igiene. Adopting the criteria of subdivision utilised by the scholar, the most widely used plants, foodstuffs and drinks are described, providing information about their botanical characteristics, their history, their chemical properties, their uses and the risks of abuse. They include, among others, sugar cane, coffee, tea, yerba mate, guarana, cocoa, tobacco, poppy, pepper, cinnamon, vanilla, cloves and absinthe.